2 Suma de Riemann
2 Suma de Riemann
2 Suma de Riemann
( )
4 2
x
∫ 2
−x +3 dx
1
∫ f ( x ) dx= n→
lim ∑ f (x i )∆ x
∞
a i=1
( )
2
x
a=1 b=4 n=5 f ( x )= −x+ 3 dx
2
( ( )
)
2
3
1+ i
f ( xi )=
2
n 3
− 1+ i +3
n ( )
( )( )
2
2 3 3
(
1 +2 1 ) i + i
n n 3
¿ −1− i +3
2 n
6 9 2
1+ i+ 2 i
n n 3
−1− i+3
2 n
5 3 9 2 3
+ i+ i− i
2 n 2 n2 n
9 2 5
f ( xi )= i +
2 n2 2
Se halla el producto f ( x i) ∙ ∆ x
f ( x i ) ∙ ∆ x=
( 29n i + 52 )( 3n )= 227n i + 215n
2
2
3
2
n
Se halla la sumatoria ∑ f (x i )∆ x
i=1
n
27 2 15
∑ (¿ 2n 3
i + )→ separamos terminos ¿
2n
i=1
n n
27 2 15
3∑
i + ∑n
2n i=1 2 n i=1
2n
3 (
27 n ( n+1 ) ( 2 n+1 ) 15
6
+ ( n ) →operando
2n )
( )( 215n n)
3 2
27 2 n +3 n +n
2n 3 6
6 (
27 2 n3 +3 n2 +n
2 n3 )( ) 15 n
2n
27
6 (3 1 15 27 81
1+ + 2 + = +
2 n 2n 2
+
27 15
+
6 12 n 12 n2 2 )
n
n
Se calcula el limite lim ∑ f ( x i )∆ x
n→ 5 i=1
Para n=5
n
81 27
lim ∑ f ( x i ) ∆ x= + +12
n→ 5 i=1 12∗5 12∗52
n
lim ∑ f ( x i ) ∆ x=13.44
n→ 5 i=1
Para n=15
n
81 27
lim
n →15
∑ f ( x i ) ∆ x= +
12∗15 12∗15 2
+12
i=1
n
lim ∑ f ( x i ) ∆ x=12.46
n →15 i=1
Para n=25
n
81 27
lim
n →25
∑ f ( x i ) ∆ x=
12∗25
+
12∗25
2
+12
i =1
n
lim ∑ f ( x i ) ∆ x=12.2736
n →25 i =1